2021
DOI: 10.1177/13591053211044535
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination policy reactance: Predictors, consequences, and countermeasures

Abstract: Ending the COVID-19 pandemic will require rapid large-scale uptake of vaccines against the disease. Mandating vaccination is discussed as a suitable strategy to increase uptake. In a series of cross-sectional quota-representative surveys and two preregistered experiments conducted in Germany and the US (total N = 4629), we investigated (i) correlates of individual preferences for mandatory (vs voluntary) COVID-19 vaccination policies; (ii) potential detrimental effects of mandatory policies; and (iii) interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 34 publications
3
52
0
3
Order By: Relevance
“…Als inhaltliches Hauptargument gegen die Impfpflicht haben wir außerdem die psychologischen Nebenwirkungen einer Impfpflicht aufgeführt: eine Impfpflicht kann bei Personen, die Impfen ablehnen, aufgrund von Reaktanz (Ärger) zu "Trotzverhalten" führen-und sich negativ auf andere Impfentscheidungen auswirken. Andere freiwillige Impfungen können dann möglicherweise ausgelassen werden als Zeichen des Widerstands und um die eingeschränkte Entscheidungsfreiheit wieder herzustellen (Betsch & Böhm, 2016;Omer et al, 2018;Sprengholz et al, 2021aSprengholz et al, , 2021b.…”
Section: Wortbruch Und Meinungsänderungunclassified
See 2 more Smart Citations
“…Als inhaltliches Hauptargument gegen die Impfpflicht haben wir außerdem die psychologischen Nebenwirkungen einer Impfpflicht aufgeführt: eine Impfpflicht kann bei Personen, die Impfen ablehnen, aufgrund von Reaktanz (Ärger) zu "Trotzverhalten" führen-und sich negativ auf andere Impfentscheidungen auswirken. Andere freiwillige Impfungen können dann möglicherweise ausgelassen werden als Zeichen des Widerstands und um die eingeschränkte Entscheidungsfreiheit wieder herzustellen (Betsch & Böhm, 2016;Omer et al, 2018;Sprengholz et al, 2021aSprengholz et al, , 2021b.…”
Section: Wortbruch Und Meinungsänderungunclassified
“…(2) Eine Impfpflicht kann psychologische Nebenwirkungen haben Die Ergebnisse psychologischer Experimente zeigen außerdem, dass Menschen, die der Impfung gegen COVID-19 kritisch gegenüberstehen und eine Impfpflicht ablehnen, sich über die Einführung einer Impfpflicht ärgern und in der Folge zum Beispiel andere freiwillige Impfungen, z.B. gegen Grippe, eher auslassen wollen (Sprengholz et al, 2021a(Sprengholz et al, , 2021b. Außerdem sinkt ihre Bereitschaft zur Einhaltung geltender Abstands-und Hygieneregeln, etwa zum Masketragen und Abstandhalten.…”
Section: Mögliche Nachteile Einer Impfpflichtunclassified
See 1 more Smart Citation
“…Indeed, psychological reactance has been empirically shown to be activated even against wellintended persuasive educational efforts and informational campaigns to sway or change dangerous or unhealthy public attitudes on various subjects [22]. In an emerging body of research on psychological reactance to mandatory vaccination policies, it was revealed that these policies can elicit psychological reactance, in light of their restrictive or undermining effects on certain established and widely held public freedoms and choices in many demo-cratic societies [23,24]. Moreover, this psychological reactance is intensified among people who are less supportive of mandatory vaccination policies and among those with lower vaccination intentions.…”
Section: Introductionmentioning
confidence: 99%
“…However, this paper argues that, whereas psychological reactance to vaccine pressure is rooted exclusively in the reaction to protect or preserve threatened freedoms, perceived COVID-19 vaccine pressure operates as an internalized emotive and cognitive reaction to societal pressure and demands in general that does not necessarily have to be tied to a perceived restriction of specific freedoms. Some prior studies, which utilized the Salzburg State Reactance Scale (as a measure of psychological reactance), examined participants' negative emotions and cognitions in direct reaction to a mandatory vaccine policy and incorporated the perception that participants' rights and freedoms were under threat of being restricted or eliminated [23,24]. Finkelstein et al [25] also measured psychological reactance as linked to reactions of constrained freedoms and choices based on a measure developed by Hong and Page [26].…”
Section: Introductionmentioning
confidence: 99%